Global Marketing Strategy and Competitive Advantage: Starbucks International Expansion Performance - Sheila Fairuz Nissa; Nabila Dwi Amalia; Novelia Muzallifah (Journal of Economic Studies, 2026)
This study examines global marketing strategies and competitive advantages in supporting Starbucks’ international expansion performance. Globalization and the development of the coffee industry have driven multinational companies not only to expand their markets but also to adapt their business strategies to the characteristics of consumers in various countries. This paper employs a literature review approach by analyzing various relevant books, journals, and scientific articles on global marketing strategies, competitive advantages, digital marketing, and Starbucks’ international expansion. The discussion reveals that Starbucks’ success in global expansion is influenced by the company’s ability to combine standardization and local adaptation strategies. Starbucks maintains its global brand identity through product quality, service, store ambiance, and customer experience, while still adapting its menu, marketing communications, and digital approaches to local culture and consumer preferences. Furthermore, Starbucks’ competitive advantage is reinforced by its premium brand image, product innovation, loyalty programs, digital marketing, and a customer experience concept that sets it apart from competitors. Nevertheless, Starbucks continues to face challenges such as competition from local brands, shifting consumer behavior, sustainability issues, and global social dynamics. Thus, an integrated, adaptive, and customer-oriented global marketing strategy is essential.